Outcomes With Multidisciplinary Cardiac Rehabilitation in Post-acute Systolic Heart Failure Patients—A Retrospective Propensity Score-Matched Study - Chen, Shyh-Ming; Wang, Lin-Yi; Liaw, Mei-Yun; Wu, Ming-Kung; Wu, Po-Jui; Wei, Chin-Ling; Chen, An-Ni; Su, Tsui-Ling; Chang, Jui-Kun; Yang, Tsung-Hsun; Chen, Ching; Cheng, Cheng-I; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiac rehabilitation (CR) is recommended for patients with acute heart failure (HF). However, the results from outcome studies and meta-analyses on CR in post-acute care are varied. We aimed to study the medium- to long-term impact of CR and determine predictors for successful CR. Methods In this propensity score matched (PSM) retrospective cohort study, consecutive patients who survived acute HF (left ventricular ejection fraction <40) and participated in a multidisciplinary HF program post-discharge were collected between May 2014 and July 2019. Patients in the CR group received at least one exercise session within 3 months after discharge; the others were in the non-CR group. After PSM, the primary (all-cause mortality) and secondary (HF readmission and life quality assessment) outcomes were analyzed. Results Of the 792 patients, 142 attended at least one session of phase II CR. After PSM for covariates related to HF prognosis, 518 patients were included (CR, 137 patients). The all-cause mortality rate was 24.9% and the HF rehospitalization rate was 34.6% in the median 3.04-year follow-up. Cox proportional hazard analysis revealed that the CR group was associated with a significant reduction in all-cause mortality compared to the no-CR group (hazard ratio [HR]: 0.490, 95% confidence interval [CI]: 0.308–0.778). A lower risk of the primary outcome with CR was observed in patients prescribed renin-angiotensin-aldosterone system (RAAS) inhibitors but not in those without prescriptions (interaction p= 0.014). Conclusions CR was associated with reduced medium- to long-term all-cause mortality under the multidisciplinary program. Our finding that the benefit of CR was decreased in patients without RAAS inhibitors warrants further evaluation.